Galacto-oligosaccharides and Colorectal Cancer: Feeding our Intestinal Probiome - Bruno-Barcena, Jose M. (J Funct Foods, 2015)
Prebiotics are ingredients selectively fermented by the intestinal microbiota that promote changes in the microbial community structure and/or their metabolism, conferring health benefits to the host. Studies show that β (1–4) galacto-oligosaccharides [β (1–4) GOS], lactulose and fructo-oligosaccharides increase intestinal concentration of lactate and short chain fatty acids, and stool frequency and weight, and they decrease fecal concentration of secondary bile acids, fecal pH, and nitroreductase and β-glucuronidase activities suggesting a clear role in colorectal cancer (CRC) prevention. This review summarizes research on prebiotics bioassimilation, specifically β (1–4) GOS, and their potential role in CRC. We also evaluate research that show that the impact of prebiotics on host physiology can be direct or through modulation of the gut intestinal microbiome, specifically the probiome (autochtonous beneficial bacteria), we present studies on a potential role in CRC progression to finally describe the current state of β (1–4) GOS generation for industrial production.